Evaluasi Kompetensi Ranah Afektif Siswa Sekolah Dasar - Heri Setiawan; Awal Nur Kholifatur Rosyidah; Ilham Syahrul Jiwandono; Itsna Oktaviyanti; Baiq Niswatul Khair; Heri Hadi Saputra; Styo Mahendra Wasita Aji (Primera Educatia Mandalika: Elementary Education Journal, 2025)
The purpose of this study is to examine and describe various assessment techniques that can be used to assess students' affective domain competencies in elementary schools. This research approach involved a literature review, examining various manuscripts on the topic of assessing affective domain competencies in elementary school students. The manuscripts were searched in leading databases such as ERIC and Google Scholar, which were then analyzed and reviewed in-depth in the discussion section. The analysis revealed that various assessment techniques can be used to assess students' character values ​​in elementary schools, including observation, self-assessment, peer assessment, and daily journals compiled by teachers.